1980
DOI: 10.1177/003151258005000232
|View full text |Cite
|
Sign up to set email alerts
|

Time Estimation among Schizophrenics

Abstract: Studies of time estimation among schizophrenics have sometimes been difficult to integrate with one another because of differing methodologies and inconsistent definitions. The present study should increase clarity by employing several methods of time estimation within the same study and maintaining a consistent definition of overestimation and underestimation across tasks. 26 schizophrenic and 26 control subjects were given three types of time-estimation tasks. Longer Interval Estimation involved judging, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Dans une étude classique, Lhamon et Goldstone (1956) démontrent que les individus d'un groupe contrôle et d'un groupe composé de schizophrènes tendent tous à surestimer un intervalle d'une seconde, mais que les schizophrènes le surestiment davantage. Depuis, plusieurs autres études ont également permis de démontrer que les schizophrènes semblent surestimer les intervalles qui leur sont présentés (Broota, Kaur & Batra, 1988; Tysk, 1983a, Tysk, 1983b; Wahl & Sieg, 1980). Cependant, trois chercheurs ont aussi observé le phénomène inverse (voir Lehmann, 1967), alors qu'une dizaine d'autres n'ont observé ni surestimation ni sous-estimation de la durée (voir Todd, Michie, Budd, Rock & Jablensky, 2000).…”
Section: Le Temps En Psychiatrieunclassified
“…Dans une étude classique, Lhamon et Goldstone (1956) démontrent que les individus d'un groupe contrôle et d'un groupe composé de schizophrènes tendent tous à surestimer un intervalle d'une seconde, mais que les schizophrènes le surestiment davantage. Depuis, plusieurs autres études ont également permis de démontrer que les schizophrènes semblent surestimer les intervalles qui leur sont présentés (Broota, Kaur & Batra, 1988; Tysk, 1983a, Tysk, 1983b; Wahl & Sieg, 1980). Cependant, trois chercheurs ont aussi observé le phénomène inverse (voir Lehmann, 1967), alors qu'une dizaine d'autres n'ont observé ni surestimation ni sous-estimation de la durée (voir Todd, Michie, Budd, Rock & Jablensky, 2000).…”
Section: Le Temps En Psychiatrieunclassified
“…Dans leur étude, les intervalles de temps pouvaient être présentés dans une modalité visuelle et/ou auditive. Leurs résultats n'ont pas montré de surestimation systématique des durées chez les patients à risque, contrairement aux résultats rapportés dans quelques études, notamment Wahl & Sieg (1980). De plus, le point d'égalité subjective (entre intervalle court et long) obtenu en modalité auditive était similaire pour les patients à risque de schizophrénie, le groupe des témoins et celui des patients souffrants de troubles de l'humeur.…”
Section: Introductionunclassified
“…They also report, at least for longer intervals, that schizophrenics' accuracy and perception of durations is not significantly different (Wahl & Sieg, 1980), which accords with current thinking that schizophrenic time perception deficits manifest in subsecond durations more strongly than suprasecond durations (Reed & Randell, 2014). Wahl & Sieg make the argument that subsecond and suprasecond durations might be served by different cognitive processes, something which Grondin (2010) discusses, at length, in his review of critical timing.…”
Section: Time Perception and Schizophreniamentioning
confidence: 59%
“…Interestingly, we can see the establishment of the idea that schizophrenics potentially possess a 'faster pacemaker', which is a conclusion that the likes of Carroll et al (2008) have reached though, it is important to say that any part of the SET process might be retarded, hence the importance of Carlson & Feinberg's (1968) work. Much of the research in the 1970s concluded that schizophrenics err in the direction of overestimation, which means that they perceive more time has passed than has elapsed in reality (Wahl & Sieg, 1980); or that time appears to be passing more slowly than is expected though, as Wahl & Sieg (1980) contend, because of methodological and terminological confusion, there is a lack of consistency among patterns, with discrepant findings (e.g., Densen, 1977). To address this, Wahl & Sieg defined 'overestimation' as having judged more time had elapsed than had objectively elapsed; and underestimation as having judged less than the actual time had elapsed.…”
Section: Time Perception and Schizophreniamentioning
confidence: 99%